Knowledge of pastoralists on livestock diseases and exposure assessment to brucellosis within rural and peri-urban areas in Kajiado, Kenya [version 1; peer review: 2 approved] - Joshua Onono; Penina Mutua; Philip Kitala; Peter Gathura (F1000Research, 2019)
Background: Livestock diseases impact the livelihoods of pastoralists. Brucellosis, a neglected zoonotic disease is highly prevalent in this system with an estimated 16% of livestock population in sub-Saharan Africa infected with the disease. The objective of this study was to assess knowledge of livestock diseases and the risk of exposure to brucellosis among pastoralists living in Kajiado County of Kenya. Methods: The study sites included pastoralist communities living in rural and peri-urban areas within the County. Both primary and secondary data were collected using participatory methods including pairwise ranking, proportional piling and probing and a review of the published literature. Exposure risk assessment was conducted according to the CODEX Alimentarius framework: Hazard identification, hazard characterization, exposure assessment and risk estimation. Results: According to pastoralists, livestock diseases that frequently occurred in their flocks and herds were contagious caprine pleuropneumonia, lumpy skin disease and foot and mouth disease; but zoonoses, including anthrax and brucellosis, were also mentioned during focus group discussions. Potential pathways of exposure to brucellosis and other zoonoses included consumption of unpasteurized milk, handling infected aborted materials without protective measures and consumption of raw meat and raw blood. Consumption of unpasteurized milk and handling infected aborted materials without protectives were linked with high risk of exposure to household members living in rural areas, with the risk level within the peri-urban areas ranked very low to low for most of these risk practices. Conclusions: The results call for enhanced public education targeting vulnerable groups to mitigate risks of disease spread and other impacts of brucellosis within the affected pastoralist production systems.